The icelandic banking crisis: would basel III have made a difference? - Silva, Ana Teresa Fortes Marques da (2017)
The purpose of this research is to understand whether the Icelandic banking crisis would have been prevented or downsized, had Basel III regulation been in place at the time. Iceland saw three of its major banks collapse in 2008. Landsbanki, one of the three biggest banks, was analyzed and its problems identified, followed by the application of Basel III regulation to its 2007’ financial statements. After applying Basel III reforms, verification of ratios compliance was performed. This research provides valuable insights on the soundness of Basel III, raising awareness for its limitations, by exposing the results of its implementation before the crisis.